Literature Review on Stages of Colorectal Cancer (International Journal of Scientific Research in Science and Technology, 2024)
Colorectal cancer, primarily originating from polyps in the colon or rectum, represents a significant health challenge due to its potential progression to malignancy. Polyps, abnormal tissue growths in the inner lining of the colon or rectum, often start as benign adenomas. Over time, these adenomas may undergo cellular mutations, transforming into cancerous tumors. Early detection and removal of polyps during screening significantly reduce the likelihood of cancer development. If left untreated, colorectal cancer can invade deeper layers of the colon wall, metastasize to nearby lymph nodes, and spread to distant organs, commonly the liver, peritoneum, or lungs. Colon cancer typically originates in the mucosa, the innermost lining of the colon, and progresses through the tissue and muscle layers over a span of approximately 10 years. The anatomy of the colon and rectum, consisting of the cecum, ascending colon, transverse colon, descending colon, sigmoid colon, and rectum, plays a critical role in understanding the disease’s progression. Advances in screening methods and treatments have significantly improved outcomes, emphasizing the importance of early intervention in reducing colorectal cancer mortality.